2012
DOI: 10.26719/2012.18.9.974
|View full text |Cite
|
Sign up to set email alerts
|

Lead exposure among the general population of Duhok governorate, Kurdistan region, Iraq

Abstract: This study was carried out to establish baseline data on lead exposure in a sample of the general population from Duhok governorate, Iraq in 2011. A cross-sectional study was made of blood lead levels of 820 individuals and of dust and of air lead levels in urban, suburban and rural residential areas. Mean blood lead (BPb) value in the overall sample was 7.3 (SD 2.8) µg/dL, range 1.6-17.0 µg/dL; significant differences were found with respect to age, area of residence, altitude and distance from a gasoline gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
(7 reference statements)
1
4
1
Order By: Relevance
“…The main sources of Pb exposure for the general population was airborne particulate (smoke included). These findings agreed well with the fact that environmental lead pollution is a major problem in our country, Beside the leaded gasoline, which was considered the major source of environmental inorganic lead exposure, this results agrees with findings of other local studies in Kurdistan region-Iraq [18] and other studies in Pakistan. [19] Duration of Work: In the current study which showed significant difference in duration of work in work place between cases and controls especially for those with more than 10 years' work.…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…The main sources of Pb exposure for the general population was airborne particulate (smoke included). These findings agreed well with the fact that environmental lead pollution is a major problem in our country, Beside the leaded gasoline, which was considered the major source of environmental inorganic lead exposure, this results agrees with findings of other local studies in Kurdistan region-Iraq [18] and other studies in Pakistan. [19] Duration of Work: In the current study which showed significant difference in duration of work in work place between cases and controls especially for those with more than 10 years' work.…”
Section: Methodssupporting
confidence: 82%
“…In Kirkuk city-Iraq, the level of atmospheric lead was 956.8 μg/m³ in 2011*. [24] This value is much higher than the mean BLLs of the general population reported in Basrah / Iraq 11.20 μg/dL [25] , this may be due to low occupational μg/dL also was very lower from our study [18] , this may be due to the origin of their sample which were taken mainly from rural and suburban regions and the nature of their geographical area as well as the low occupational exposure. Among all participants in this study the mean BLLs value in controls group were 12.349 μg/dL.…”
Section: Methodscontrasting
confidence: 52%
“…The systematic synthesis was carried out in only 34 studies that passed the MMAT analysis. The distribution of polluted sources of lead MENA was obtained from Iran (n = 9); Malekirad AA et al[63] 2013, Raissy M [78] 2016, Khatibi-Moghadam H et al [79] 2016, Daneshparvar M et al [89] 2016, Ahmadi M et al [81] 2017, Vahidinia A et al [82] 2018, Soltaninejad K et al [87] 2018, Mayel M et al [90] 2020, Samarghandian S et al [88] 2021; Saudi Arabia (n = 6); Al-Saleh I et al [43] 1996, Al-Saleh I et al [57] 2008, Zolaly MA et al [60] 2012, Ashraf MW et al [61] 2012, Salama AK et al [75] 2016, Chowdhury S et al [83] 2018; Lebanon (n = 5); Nuwayhid I et al [47] 2001, Nuwayhid I et al [51] 2003, Nasreddine L et al [53] 2006, Korfali SI et al [64] 2013, Bassil M et al [84] 2018; Egypt (n = 3); Mortada WI et al [49] 2001, Mandour RA et al [65] 2013, Moawad EM et al [77] 2016; Kuwait (n = 2); Shaltout A et al [41] 1981, Jallad KN et al [56] 2008; Morocco (n = 2); Bouftini S et al [66] 2014, Laamech J et al [68] 2014; Algeria (n = 1); Cher A et al [69] 2014; Iraq (n = 1); Al-Dosky AH et al[59] 2012; Israel (n = 1);Greenberg N et al [76] 2016; Jordan (n = 1); Nusier MK et al[50] 2003; Oman (n = 1); El Tawila M resources, including cosmetics[41,43,51, 56,57, 60,75, 82], socio-economic and cultural[43, 84], and occupational sources that negatively affected both children and adults of both genders[47, 48,49,50, 63,70, 76,77, 88], residential factors that were not limited to paints, but extend to overseas the whole condition of a building (building age, status, ventilation, and whether it near to a generating lead source of pollution) [51, 59, 66, 68, 77, 84, 88], cooking habits[51, 60], oral intake of polluted lead substances[60, 83, 88…”
mentioning
confidence: 99%
“…The residential genre is not an absolute one factor; it co-exists with the environmental genre. An Iraq-based study by Al-Dosky AH et al[59] in 2012 comprised 820 individuals living in urban, suburban, and rural areas. Age, place of residence, altitude, and distance from a gasoline generator all showed signi cant variances.…”
mentioning
confidence: 99%
“…The systematic synthesis was carried out in only 34 studies that passed the MMAT analysis. The distribution of polluted sources of lead MENA was obtained from Iran (n = 9); Malekirad AA et al[63] 2013, Raissy M [78] 2016, Khatibi-Moghadam H et al [79] 2016, Daneshparvar M et al [89] 2016, Ahmadi M et al [81] 2017, Vahidinia A et al [82] 2018, Soltaninejad K et al [87] 2018, Mayel M et al [90] 2020, Samarghandian S et al [88] 2021; Saudi Arabia (n = 6); Al-Saleh I et al [43] 1996, Al-Saleh I et al [57] 2008, Zolaly MA et al [60] 2012, Ashraf MW et al [61] 2012, Salama AK et al [75] 2016, Chowdhury S et al [83] 2018; Lebanon (n = 5); Nuwayhid I et al [47] 2001, Nuwayhid I et al [51] 2003, Nasreddine L et al [53] 2006, Korfali SI et al [64] 2013, Bassil M et al [84] 2018; Egypt (n = 3); Mortada WI et al [49] 2001, Mandour RA et al [65] 2013, Moawad EM et al [77] 2016; Kuwait (n = 2); Shaltout A et al [41] 1981, Jallad KN et al [56] 2008; Morocco (n = 2); Bouftini S et al [66] 2014, Laamech J et al [68] 2014; Algeria (n = 1); Cher A et al [69] 2014; Iraq (n = 1); Al-Dosky AH et al[59] 2012; Israel (n = 1);Greenberg N et al [76] 2016; Jordan (n = 1); Nusier MK et al[50] 2003; Oman (n = 1); El Tawila M resources, including cosmetics[41,43,51, 56,57, 60,75, 82], socio-economic and cultural[43, 84], and occupational sources that negatively affected both children and adults of both genders[47, 48,49,50, 63,70, 76,77, 88], residential factors that were not limited to paints, but extend to overseas the whole condition of a building (building age, status, ventilation, and whether it near to a generating lead source of pollution) [51, 59, 66, 68, 77, 84, 88], cooking habits[51, 60], oral intake of polluted lead substances[60, 83, 88…”
mentioning
confidence: 99%